Inulin and Oligofructose: Review of Experimental Data on Immune Modulation - Seifert, Stephanie; Watzl, Bernhard (The Journal of nutrition, 2007)
Diet modulates immune functions in different ways and affects host resistance to infections. In addition to the essential nutrients in food, nonessential food constituents such as nondigestible carbohydrates also affect the immune system. First results from human intervention studies suggest that the intake of inulin (IN) and oligofructose (OF) has beneficial effects on the gut-associated lymphoid tissue. At the level of the systemic immune system, however, only minor effects have been observed in healthy adult human subjects. In contrast, data from studies with infants suggest that supplementation with a prebiotic mixture positively affects postnatal immune development and increases fecal secretory IgA. Animal studies confirm the observations from human trials and give more insight into the immune tissue- specific effects of IN/OF. A clear outcome of the animal studies is that the intestinal immune system and especially the immune cells associated with the Peyer's patches are responsive to a dietary supplement of IN/OF and/or their metabolites. The mechanisms of IN/OF include indirect effects such as a shift in the composition of the intestinal flora and the enhanced production of immunoregulatory SCFA and perhaps other bacterial metabolites. Few data suggest direct effects of IN/OF via carbohydrate receptors on intestinal epithelial cells and immune cells. In conclusion, prebiotic IN/OF clearly modulate immunological processes at the level of the gut-associated lymphoid tissue, which may be associated with significant health benefits in infants and patients with intestinal inflammatory diseases.